Prevalence and Injury Risk Factors based on Sleman Health and Demographic Surveillance System (HDSS) Data - Idha Arfianti Wiraagni1 , Beta Ahlam Gizela1 , Majid2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Injuries can occur in various groups of individuals with various risk factors and complications.Health problems due to injuries will put a burden on the victims’ individuals and families, health services,health insurance, even various parties related to the work productivity of victims. The analysis of injury riskfactors is an initial effort for injury prevention efforts which are expected to avoid reducing productivityand quality of life of individuals. Problem: Need to explore and analyze risk factors for injury, includingdemographic profile. Objective: The research to be carried out to determine the prevalence of injury casesand risk factors. Methods: This study used a cross-sectional observational design. The data used is secondarydata from HDSS Sleman. Research subjects were all injury cases recorded in the Sleman HDSS document.Statistical analysis was performed to calculate prevalence and see the strength of the relationship betweenrisk factors and the incidence of injury. Results: Males had an accident 54%, in 2017, it rose to 56%, and in2019 it dropped to 55%. In 2016, adults suffered 48% injuries, then decreased to 38% and 36% in the nextcycle. In 2016, the number of bruises and abrasions was 72%, and decreased in the next two cycles of 67%and 58%. Part of the body that was most often affected by injury during three cycles was the upper limb.Conclussion : Continued research on injuries and associated risk factors, needs to be done to create healthsurveillance data.